Excited State Frequencies of Chlorophyll f and Chlorophyll a and Evaluation of Displacement through Franck-Condon Progression Calculations - Zamzam, Noura (Molecules, 2019)
We present ground and excited state frequency calculations of the recently discovered extremely red-shifted chlorophyll f. We discuss the experimentally available vibrational mode assignments of chlorophyll f and chlorophyll a which are characterised by particularly large downshifts of 13(1)-keto mode in the excited state. The accuracy of excited state frequencies and their displacements are evaluated by the construction of Franck–Condon (FC) and Herzberg–Teller (HT) progressions at the CAM-B3LYP/6-31G(d) level. Results show that while CAM-B3LYP results are improved relative to B3LYP calculations, the displacements and downshifts of high-frequency modes are underestimated still, and that the progressions calculated for low temperature are dominated by low-frequency modes rather than fingerprint modes that are Resonant Raman active.